Analisis Statik Kekuatan dan Tingkat Keamanan pada Spring Plate Girth Gear Kiln Pabrik Indarung V PTSP - Lovely Son; Meifal Rusli; Dorce Yunirsyam (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
This research discusses the static analysis of the kiln girth gear at Indarung cement Factory V PTSP due to replacement of the oldest girth gear with the newest one. The newest version of girth gear system has a smaller number of supporting spring (spring plate) in comparison with the previous one. Therefore, it is necessary to analyze the effect of the spring plate number to the strength and stiffness of the girth gear system to assure the kiln can work properly. In this research the effect of the spring plate number to the linear and torsional stiffness of the girth gear is evaluated. Based on the simulation results, decreasing of the spring plate number from 16 to 12, significantly affect the total stiffness of the supporting spring. Furthermore, it was found from the simulation that the total stiffness of the supporting spring much affected by the axial stiffness of the spring plate comparing to its lateral stiffness.